Tectonic Control on the Formation of Cleats in the Coal Beds of the Sajau Formation, Berau Basin, Northeast Kalimantan - Sudradjat, Adjat; Hamdani, Ahmad Helman (Geological Agency, 2018)
DOI: 10.17014/ijog.5.3.235-250Coal seams of lignite- to subbituminous rank of Pliocene-age from the Sajau Formation of the Berau Basin are characterized by the presence of a natural fracture system, including cleats. Often, these opening-mode fractures consist of two orthogonal sets (face and butt cleats), both almost perpendicular to the bedding. This paper describes the distribution of orientation, spacing, and aperture of cleats formed in the seams of the Sajau Formation. All observations and measurements were conducted at macroscopic, mesoscopic, and microscopic scales. The butt cleat mean orientations are NE-SW and NW-SE, whereas the face cleat mean orientations are NNE-SSW and NE-SE, and the cleat dip is at a high angle of 75° to the north. The angles between the orientations of these cleat sets are nearly 90°; that is, they are orthogonal. The spacing of the macroface cleats is between 9.52 and 14.46 cm (averaging 11.61 cm), while the spacing of the butt cleats is between 2.3 and 11.3 cm (averaging 5.35 cm). The mean aperture is 0.54 mm. In contrast, the mean spacing of the mesoface cleats is 3.09 mm, and the aperture measurements of these cleats range from 0.0478 to 0.0741 mm (averaging 0.0549 mm). The results obtained from outcrops and X-ray CT (computed tomography) scan clearly indicate that the NNE-SSW face cleat orientations are strictly parallel to the elongation of the main tectonic structures in the studied area. Their origin may be explained by their relationship with local tectonic stress (the maximum principal stress, σ1, was horizontal). Partial least square analysis of data collected from cleats and faults in the area indicates that a power law distribution exists between the cleat characteristics (spacing, density, and aperture), and the distance of the faults (R2 = 0.56). Cleat formation in the Sajau Formation was mainly controlled by the mechanical response to tectonic stresses, which generated a unique cleat network in the coal. Based on the SEM photography, it is concluded that the development of microcleats in the Sajau Formation resulted from both endogenic processes and tectonic activities as indicated by the change in the shape of the cleats, from straight line to curved shape and branching (intersection of multiple cleats that form a conical network at the end).